A Review: AmpC β-lactamase production in Enterobacteriaceae - Santiago, Gabrielli S.; da Motta, Cássia C.; Bronzato, Greiciane F.; Gonçalves, Daniela; de Souza, Miliane M. Soares; Coelho, Irene da Silva; Ferreira, Helena Neto; Coelho, Shana de Mattos de Oliveira (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Santiago G.S., Motta C.C., Bronzato G.F., Gonçalves D., de Souza M.M.S., Coelho I.daS., Ferreira H.N. & Coelho S.deM.deO. [A Review: AmpC β-lactamase production in Enterobacteriaceae.] Revisão: Produção de β-lactamases do Tipo AmpC em Enterobacteriaceae. Revista Brasileira de Medicina Veterinária, 38(supl. 3):17-30, 2016. Programa de Pós-Graduação em Ciências Veterinárias, Anexo 1, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, BR465, Km 7, Campus Seropédica, RJ, 23890-000, Brasil. E-mail: gabriellissantiago@outlook.com AmpC β-lactamases are relevant enzymes produced constitutively or induced by chromosomal or plasmid genes expressed by members of Enterobacteriaceae family and other Gram negative bacteria. Producers of this type of β-lactamase hydrolyze almost all β-lactam antibiotics including cephalosporins, cephamycins, penicillins and combinations with β-lactamase inhibitors, limiting therapeutic options to treat infections caused by these resistant bacteria. In addiction some mutations can induce appearance of an extended-spectrum AmpC (ESAC) that is able to hydrolyze four generation cephalosporins and carbapenems, and that phenomenon already has been detected in cattle. Small differences in the amino acid sequence characterize families and types of AmpC, with CMY-2 prevalent in isolates from pet and food animals in world. Presence of AmpC is often associated with multidrug resistance due to the copresence of other resistance genes in the same plasmid that confer resistance to the most varied classes of antimicrobials i.e aminoglycosides, quinolones, sulfonamides and tetracyclines. There are few antimicrobial agents safely effective against these isolates and many of them are not available or are not approved for animal use. Different detection methods are available, however the lack of international standardization limits the reporting of AmpC by clinical laboratories, which may underestimate this mechanism of resistance.